PENGARUH STRUKTUR ORGANISASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERSADA INDONESIA - Defanny, Fiola Devita; Rini, Hesty Prima (POLITEKNIK LP3I JAKARTA, 2026)
The decline in employee performance is evident in the failure to achieve established work targets. Over the past two years, the company has undergone changes to its organizational structure and systems. This study aims to examine the influence of organizational structure, leadership, and the work environment on employee performance at Persada Indonesia. The study used a quantitative approach with a saturated sampling technique involving all 50 employees as respondents. Data were collected through questionnaires, then analyzed using the Partial Least Squares (PLS) method. The results show that organizational structure, leadership, and the work environment have a positive and significant influence on employee performance. These findings confirm that targeted change management, communicative leadership, and a conducive work environment are important factors in efforts to improve employee performance.